Consider the transformations outlined below. Homework Help ✎
How is the graph of f(x) =
transformed to obtain the graph of g(x) = – 3?
How is the graph of y = x2 transformed to obtain the graph of y = –(x – 1)2 + 20?
How is the graph of y =
transformed to obtain the graph of y = –3 ?
There will be a vertical shift and a horizontal shift.
f is translated 2 units left and 3 units down to obtain g.
To get the second graph, the first graph is vertically stretched by factor of 3, reflected
across the x-axis, and translated left 71 units.